Calculating the Pitch of a Serrated-Type Rotary Tiller - P. I. Gadzhiev; M. M. Makhmutov; A. I. Alekseev; M. M. Makhmutov (Сельскохозяйственные машины и технологии)
The high energy intensity associated with rotary tillage of soil serves as a deterrent for its widespread use. Rotary tillers are used in cases when there are no alternatives as to the soil quality, especially when machining hard and sod-covered soils. The authors have described new modernized rotary tillers of a serrated type and considered the optimal location of knives relative to the drum. (Research purpose) To determine the relationships for calculating the pitch of a serrated-type rotary tiller for soil preparation before potato planting. (Materials and methods) The authors have noted that currently, there are no methods for selecting the main parameters and operation modes of serrated-type rotary tillers. The research has proved that a new approach is required for selecting the working surface profile of the rotary tiller knife in order to reduce the energy consumption of tillage and improve its quality. The authors have used mathematical and graphical calculations to determine the optimal pitch of the tiller foot. (Results and discussion) The paper presents an expression for determining the amount of soil loosening during the operation of rotary tillers. It has been calculated that an increase in the tillage depth from 0.10 to 0.15 meters results in an increase in the pitch of a tiller foot from 0.04 to 0.06 meters and the optimal value is 0.05 meters. For approximate engineering calculations, it has been assumed that the optimal parameter of a foot pitch is 0.25-0.45 of the knife loading value. (Conclusions) It has been found that the number of knives in one section and the operating width of a knife do not affect the optimal tooth pitch. It has been determined that this indicator linearly depends on the depth of tillage: as it increases by 0.05 meters, the optimal foot step increases by 0.025 meters. It has been shown that as the working speed of the rotary tiller increases, specific energy consumption required for the treatment of a furrow slice decreases, and the efficiency of soil tillage improves.